2000
DOI: 10.1292/jvms.62.293
|View full text |Cite
|
Sign up to set email alerts
|

Histological Disorders Related to the Focal Disappearance of the Epiphyseal Growth Plate in Rats Induced by High Dose of Vitamin A.

Abstract: ABSTRACT. The histological disorders related to the focal disappearance of the epiphyseal growth plate were examined histochemically in the proximal tibia of rats administered a high dose of vitamin A. Animals were given 100,000 IU/100 g body weight/day of vitamin A for 5 days from 4 weeks after birth (VA rats) or given deionized water as control and sacrificed on Day 12 and 19 of the experiment. Tibiae were examined by immunohistochemistry for type I, II and X collagens, lectin-histochemistry for Helix pomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…In addition to reduction of the hypertrophic cell zone, tearing of hypertrophic cell with signs of degeneration were observed. These findings are similar with studies that clarified that hypervitaminosis A induced chondroclast cells to absorb the calcified cartilage matrix and result in the erosions of hypertrophic zone (27,28).Also, Firat.D, Kuntsal .L and Sirin. Y,2005, had reported that Retinoic acid induced chondrocytes degeneration of fetal Meckel's cartilage (29).…”
Section: Discussionsupporting
confidence: 89%
“…In addition to reduction of the hypertrophic cell zone, tearing of hypertrophic cell with signs of degeneration were observed. These findings are similar with studies that clarified that hypervitaminosis A induced chondroclast cells to absorb the calcified cartilage matrix and result in the erosions of hypertrophic zone (27,28).Also, Firat.D, Kuntsal .L and Sirin. Y,2005, had reported that Retinoic acid induced chondrocytes degeneration of fetal Meckel's cartilage (29).…”
Section: Discussionsupporting
confidence: 89%
“…On the 12 th day, it appeared that abnormal cartilage matrix had developed in the epiphyseal growth plate of rats administered vitamin A. On the 19 th day there was a reduction in columnar arrangement and one or two focal losses in the epiphyseal growth plate of all rats administered vitamin A. Additionally, the calcified cartilage matrix surfaces were covered with a fine layer of bone tissue [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous publications have shown that high dose vitamin A use reduces the epiphyseal growth plate [ 11 13 ]. Some publications have shown that excess vitamin A increases the number and volume of osteoclasts, reducing the osteoid surface causing bone resorption [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lectin-histochemistry for griffonia simplicifolia lectin (GSL)-I Lectin-histochemistry was performed according to Soeta et al (2000). Briefly, after blocking of endogenous peroxidase activity, sections were treated with 1% bovine serum albumin in 0.01 M phosphate-buffered saline (PBS; pH 7.4).…”
Section: Animalsmentioning
confidence: 99%